1971
DOI: 10.1007/bf01254676
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the properties of five pox virus strains isolated from monkeys

Abstract: Five strains of monkey pox viruses were compared with respect to their cultural characteristics in primary and continuous cell cultures and the lesions developed in embryonated eggs and in rabbit skin as well as to their hemagglutinating activity.Four strains ("Copenhagen"; "65-31"; "65-32" and "7-61") appeared to be similar in their properties. The cytopathogenic effect (CPE) was identical to that induced by vaccinia virus. There was no detectable virus multiplication in an pig kidney cell line (PEK). All fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
2

Year Published

1973
1973
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 3 publications
0
18
0
2
Order By: Relevance
“…CPE has not been observed in our laboratory in Hep-2 cells, certain lines of HeLa cells, and chicken embryo cell cultures (66), although others (48,70) have reported CPE in these cell cultures. Marennikova et al (48) reported that a strain of MPV "64-7275" had all the properties of variola virus and was unable to replicate in a continuous line of pig embryonic kidney cells which supported four other strains of MPV.…”
Section: Monkeypox Virus As An Infectious Agent Physical and Chemicalmentioning
confidence: 68%
See 1 more Smart Citation
“…CPE has not been observed in our laboratory in Hep-2 cells, certain lines of HeLa cells, and chicken embryo cell cultures (66), although others (48,70) have reported CPE in these cell cultures. Marennikova et al (48) reported that a strain of MPV "64-7275" had all the properties of variola virus and was unable to replicate in a continuous line of pig embryonic kidney cells which supported four other strains of MPV.…”
Section: Monkeypox Virus As An Infectious Agent Physical and Chemicalmentioning
confidence: 68%
“…These cultured cells include primary and secondary lines of kidney cells derived from rhesus, cynomolgus, and African green monkeys (20,49,66,70); cells from rabbit, bovine (49,66) and guinea pig kidneys (48); mouse liver cells (66); and some of human origin, i.e., amnionic and human lung fibroblasts (31,48,66,70). CPE has not been observed in our laboratory in Hep-2 cells, certain lines of HeLa cells, and chicken embryo cell cultures (66), although others (48,70) have reported CPE in these cell cultures. Marennikova et al (48) reported that a strain of MPV "64-7275" had all the properties of variola virus and was unable to replicate in a continuous line of pig embryonic kidney cells which supported four other strains of MPV.…”
Section: Monkeypox Virus As An Infectious Agent Physical and Chemicalmentioning
confidence: 99%
“…Die Flaumfedern der lateralen Seite des rechten Beines wurden ausgezupft und anschliei3end in die Hautflache mittels einer Pipettenspitze 0,05 ml des Impfmaterials intensiv eingerieben. (1,3,7,9,15,17,20,28,30). Sieht man von den nicht immer auftretenden zentralen Nekrosen bei den V-Stammen, den nicht regelmai3igen hamorrhagischen Tendenzen und gewissen durchschnittlichen Groi3enschwankungen bei den V-, KP-, BP-und EP-Stammen ab, dann liei3en sich anhand der Herdmorphologie auf der CAM nur AP und CP von den anderen Arten spontan unterscheiden.…”
Section: Versuchstiere Und Infektionstechnikunclassified
“…Der sonst typisch reagierende Stamm AP-3 liei3 sich in HEF-Kulturen nur schwer und ohne cpE vermehren. Bei AP-Stammen, die die charakteristischen Variola-ahnlichen CAM-Herde hervorriefen (7, 26, 30), wurde einmal eine hamorrhagische Komponente beschrieben (30). Die gleichen Stamme, Copenhagen (AP-l), ,,65-31" (AP-4), ,,65-32" (AP-2) und ,,64-7275" (AP-3) verhielten sich aber in den eigenen Untersuchungen nicht abweichend von der AP-ty ischen nicht…”
Section: Verhalten Am Kaninchenunclassified
“…During 1968-1970 among the strains re ceived by us for assay as monkeypox viruses, two isolates from monkey kidney cell cul ture were detected which differed strikingly from the others and which appeared to be identical by laboratory markers to variola virus [1][2][3]. Later, four similar viruses were isolated by us from kidneys of wild monkeys and rodents captured in Central Africa in areas where human cases of monkeypox had occurred [3][4][5][6][7].…”
mentioning
confidence: 99%